2022
DOI: 10.3748/wjg.v28.i3.348
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin prevents oxidative stress, inflammatory activity, and DNA damage in cirrhotic rats

Abstract: BACKGROUND Cirrhosis is an important health problem characterized by a significant change in liver parenchyma. In animals, this can be reproduced by an experimental model of bile duct ligation (BDL). Melatonin (MLT) is a physiological hormone synthesized from serotonin that has been studied for its beneficial properties, including its antioxidant potential. AIM To evaluate MLT’s effects on oxidative stress, the inflammatory process, and DNA damage in an experimental mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 50 publications
1
22
1
Order By: Relevance
“…DNA damage in blood was also observed in NASH mice, showing that the in ammation processes elicited in NASH might affect other tissues besides liver, although no increase in MNPCE in the NASH group was observed, showing that the bone marrow cells were not affected by the systemic injuries triggered by the disease. Conversely, in our previous studies, cirrhotic rats have not shown an increase in DNA damage in blood cells, but the MNPCE frequency increased [23][24][25]. These ndings suggest that in the course of progression from NASH to cirrhosis the damaged blood cells could be removed or repaired, however the higher liver injuries in cirrhotic rats in comparison to NASH lead to systemic repercussions able to increase the genomic instability detected using the micronucleus test.…”
Section: Discussioncontrasting
confidence: 53%
See 3 more Smart Citations
“…DNA damage in blood was also observed in NASH mice, showing that the in ammation processes elicited in NASH might affect other tissues besides liver, although no increase in MNPCE in the NASH group was observed, showing that the bone marrow cells were not affected by the systemic injuries triggered by the disease. Conversely, in our previous studies, cirrhotic rats have not shown an increase in DNA damage in blood cells, but the MNPCE frequency increased [23][24][25]. These ndings suggest that in the course of progression from NASH to cirrhosis the damaged blood cells could be removed or repaired, however the higher liver injuries in cirrhotic rats in comparison to NASH lead to systemic repercussions able to increase the genomic instability detected using the micronucleus test.…”
Section: Discussioncontrasting
confidence: 53%
“…Similarly, diseases involving an in ammatory process might increase the genomic instability detectable using the micronucleus test [21,59,60]. As already mentioned, no genomic instability was detected in the NASH model induced-MCD diet under conditions of the present study using micronucleus test in bone marrow, differently from other liver injury models such as cirrhosis induced by secondary bile duct ligation model [23][24][25], suggesting that genomic instability increases according to the progression of liver disease stages.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Moreover, melatonin will activate the antioxidant transcription factor (Fernández-Palanca et al 2021 ; Colares et al 2022 ), NRF2, which itself will start the ROS scavenging cascade. So according to our first findings, melatonin appears to act as an anti-drug resistance agent, recover the bad side effects of chemotherapy, could sensitize the cells for anti-tumor drugs, and could be administrated individually, or in combination, or post-chemotherapies as a promising supplementary component that will reduce, and minimize the side-effects of anticancer drugs.…”
Section: Discussionmentioning
confidence: 99%